Effects of M1 and CCK antagonists on latency of pancreatic amylase response to intestinal stimulants - Niebergall-Roth, Elke; Teyssen, Stephan; Singer, Manfred V. (American journal of physiology. Gastrointestinal and liver physiology, 2000)
In six conscious dogs with gastric and duodenal cannulas, secretin (164 pmol · kg−1 · h−1 iv) was given to provide a flow of pancreatic juice of ∼1 drop/s. Amylase activity was measured in each drop before and after rapid intravenous injection of caerulein (7.4 pmol/kg) or intraduodenal injection of l-tryptophan (1 mmol), sodium oleate (3 mmol), and HCl (3 mmol). All experiments were repeated in the presence of the M1 receptor antagonist telenzepine (81 nmol · kg−1 · h− iv) and the cholecystokinin (CCK) receptor antagonist L-364718 (0.1 mg/kg iv). Latency of amylase response (time between injection of stimulant and sustained increase in amylase activity greater than mean + 3 SD of prestimulatory activity) to tryptophan (17 ± 7 s;n = 6) and oleate (16 ± 5 s) was significantly (P < 0.05) shorter than to caerulein (28 ± 4 s) and HCl (120 ± 47 s). Telenzepine significantly increased the latency of amylase response to tryptophan and oleate by >10-fold but not the latency to caerulein or HCl. L-364718 abolished the amylase response to all stimulants. These findings indicate that the early amylase response to intraduodenal tryptophan and oleate is mediated by a neural enteropancreatic reflex ending on M1 receptors rather than by hormone release. However, the activation of (possibly vagal) CCK receptors is essential to run the reflex. The early amylase response to intraduodenal HCl is probably mediated by the release of CCK into the blood circulation.